IPTEKS PENERBITAN SURAT PERMINTAAN PENJELASAN ATAS DATA DAN ATAU KETERANGAN (SP2DK) OLEH ACCOUNT REPRESENTATIVE DI KANTOR PELAYANAN PAJAK PRATAMA MANADO - Kowel, Viva A. A.; Sondakh, Thessa F. Y.; Pua, Ailling I.; Budiarso, Novi S. (Universitas Sam Ratulangi, 2018)
Tax has great contribution on the development in Indonesia. Therefore, the supervision for tax obligation fulfillment is a must. In fulfilling their tax obligation, taxpayers are supervised by Account Representative to ensure they are obedient in paying taxes. One way for Account Representative to supervise taxpayers is by issuing SP2DK. Account Representative will conduct analysis on taxpayer’s data and clarification. The authority expects that an effective issuance of SP2DK will increase the tax revenue of KPP Pratama Manado. Unfortunately, in its practice there are still factors that obstruct the issuance process of SP2DK and the tax revenue realization after SP2DK is issued. Due to these facts, Account Representative is required to have good knowledge and skill in analyzing and comparing the data from taxpayer to maximize tax revenue from SP2DK issuance. Keywords : SP2DK, Account Representative, analysis, income, maximization